2010
DOI: 10.1152/jn.00226.2010
|View full text |Cite
|
Sign up to set email alerts
|

Tinnitus, Diminished Sound-Level Tolerance, and Elevated Auditory Activity in Humans With Clinically Normal Hearing Sensitivity

Abstract: Gu JW, Halpin CF, Nam E-C, Levine RA, Melcher JR. Tinnitus, diminished sound-level tolerance, and elevated auditory activity in humans with clinically normal hearing sensitivity. J Neurophysiol 104: 3361-3370, 2010. First published September 29, 2010 doi:10.1152/jn.00226.2010. Phantom sensations and sensory hypersensitivity are disordered perceptions that characterize a variety of intractable conditions involving the somatosensory, visual, and auditory modalities. We report physiological correlates of two per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
247
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 273 publications
(273 citation statements)
references
References 40 publications
19
247
1
Order By: Relevance
“…If SLT had been ignored, and the two tinnitus groups (high and low SLT) had been compared with the two no-tinnitus groups, little or no difference in contralateral suppression would have been found. An important point is that lowered tolerance of sound was not usually reported spontaneously by the low-SLT subjects of the present study (see also Gu et al 2010Gu et al , 2012. Lower tolerance only became apparent through questionnaire responses and LDL measurement.…”
Section: Discussionmentioning
confidence: 43%
See 2 more Smart Citations
“…If SLT had been ignored, and the two tinnitus groups (high and low SLT) had been compared with the two no-tinnitus groups, little or no difference in contralateral suppression would have been found. An important point is that lowered tolerance of sound was not usually reported spontaneously by the low-SLT subjects of the present study (see also Gu et al 2010Gu et al , 2012. Lower tolerance only became apparent through questionnaire responses and LDL measurement.…”
Section: Discussionmentioning
confidence: 43%
“…The SLT questionnaire consisted of three items about sound tolerance in everyday life (Gu et al 2010;Tyler et al 2003). Subjects rated their agreement with the following statements on a scale from 0 (completely disagree) to 100 (completely agree): 1) Many everyday sounds are unbearably loud to me; 2) Sounds that others believe are moderately loud are too loud for me; and 3) I hear very soft sounds that others with normal hearing do not hear.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of FA imaging to reveal hyperactive auditory brainstem circuits in vitro is an important advancement in the field of tinnitus. Although hyperactivity may or may not be the cause of tinnitus (29,30), hyperactivity provides a reliable marker of tinnitus that has also been seen in the inferior colliculus and the auditory cortex (13,23,(31)(32)(33). Given that FA imaging allows for measurement of circuit activity levels at different auditory nuclei within the same animal, FA imaging experiments in vitro are expected to provide information about the development of tinnitus.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, FA imaging has advantages over other imaging techniques that exploit intrinsic signals. PET and MRI studies have shown elevated blood flow and increased sound-evoked blood oxygenation leveldependent (BOLD) responses in central auditory structures of individuals experiencing tinnitus (9,10,23). Although PET and MRI rely on intrinsic changes, they are not suitable for mechanistic studies, unlike FA imaging, which allows us to address mechanistic details of tinnitus induction and expression.…”
mentioning
confidence: 99%